Automatic picture quality checking for VCR production - Maung Than Tun. (2008)
The purpose of this project is to explore methods to automatically check the picture quality of VCRs (video cassette recorders) in a production line. To check the picture quality of a VCR automatically, various test patterns of video signals are recorded and played back by the VCR. The video output of the VCR is digitized. Digitized video data are then analyzed by a computer. However in this project, video data are simulated by software. The program that generates the video data is able to simulate realistic data incorporating different levels of noise and errors. The analysis software reads in the video data and calculates the various video parameters that affect the picture quality. The parameters are then compared to the specifications of the VCR as part of the quality control measures. The system developed also allow users to observe the effect on video picture quality with various levels of parametric degradation. The video data are decoded to RGB levels and then converted to bitmap files so that the picture can be viewed on a PC monitor. This project was undertaken as an explorative study. The ultimate objective is to eventually integrate it into an actual production environment. The integration of the automated checking process onto the production floor should be a reasonably straightforward procedure from a technical point of view. As it is, the system developed is suitable for training purposes. It is able to simulate realistic scenarios of VCR signals to train new and inexperienced inspection operators. Such a system is useful with potential long term cost-savings in a VCR production plant.